Synthesis of PEGylated polyamidoamine (PAMAM) dendrimer - Khoa, Nguyen Cuu; Uyen, Ly Tu; Quynh, Do Nhu (Vietnam Journal of Chemistry, 2012)
PEGylated polyamidoamine dendrimer was designed as a novel drug carrier which possessed an interior for encapsulation of drugs and a biocompatible surface. This paper describes the synthesis of PEGylated polyamidoamine dendrimer, in which monomethoxy polyethylene glycol (MPEG) with the average molecular weight of 5000D was attached to the surface groups of polyamidoamine (PAMAM) dendrimer of the second and third generations. The structures of these products were confirmed by FT-IR, 1H-NMR, 13C-NMR, and Gel Permeation Chromatography (GPC).